RITUAL RAMBUT GEMBEL DALAM ARUS EKSPANSI PASAR PARIWISATA - Moh. Soehadha (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
This article focusing on religious and social change in Dieng tourism society and its relation with state capitalism. The government has commercialize gembel hair ritual (ritual rambut gembel) by tourism policy, that long have been live in Dieng community. In this article indicated that there are two variants of the social response to the change, the people who accept and reject society. The receiving society is the people that having an interest in economic on activities of the tourism development, whereas the rejecter society is the people that hold belief and tradition faithful. Theoretically, this study gives an explanation that public religiosity into the value system which affect people’s behavior to confirm the mode of economic production runs, as well as oversee social change.